Implementation of Character Strengthening and Development of Students' Critical Awareness in the Learning Process at Junior High School - sulastri, saptiana; Thamimi, Muhammad (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to explore the implementation of character strengthening programs and the development of students' critical awareness in the learning process at the junior high school level. This study used a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and document analysis. The results revealed that the character strengthening program is implemented through extracurricular activities that focus on developing students' creativity and social skills. On the other hand, the development of students' critical awareness is integrated in a learning approach that encourages active involvement, open discussion, and the utilization of various relevant learning resources. The program has shown positive impacts, including improved social skills, critical thinking skills, and student motivation to learn. However, there are several obstacles in implementing the program, including limited time for extracurricular activities and limited supporting resources. Therefore, further efforts are needed to overcome these constraints to improve the effectiveness of the implementation of character strengthening and critical awareness programs in junior high schools.